A prospective study to evaluate the effects of acute normovolemic hemodilution on perioperative homologous transfusion requirements in patients undergoing major surgery - Kumar, Ajay; Singh, Shalendra; Bhatia, Parmeet; Hooda, Bhavna; Taank, Priya (International Journal of Research in Medical Sciences, 2020)
Background: Acute Normovolemic Hemodilution (ANH) and autologous transfusion can mitigate the harmful effects of banked blood intraoperatively. This study was planned to evaluate its effects on perioperative transfusion requirement, hemodynamic stability and safety profile. Methods: Hundred patients were randomized to Group 1, where assigned patients received ANH and autologous transfusion after hemostasis; and Group II where assigned patients received homologous transfusion. In group I, 350 to 700 ml of patient’s blood was collected before induction of anaesthesia and was kept in the operation theatre at room temperature. This was followed by rapid infusion of calculated Hetastarch. Intraoperative blood loss, amount of transfused blood, serial haemoglobin (Hb) assessment, and change in hemodynamics were carefully monitored. The blood was reinfused once hemostasis was secured at the end of surgery. Results: It was observed that hemodynamic stability was maintained in both the groups during and after haemodilution. There was no significant change in bleeding and clotting time due to haemodilution. The mean intra-operative blood loss in both groups was comparable. 350 mL and 700 mL blood withdrawn in 27 and 23 patients and 500mL and 1000 mL HES infused respectively. There was an average fall in the mean Hb level by 1.74 gm % and in the mean haematocrit (Hct) level by 6.4 % after haemodilution. The mean 12th and 24th hour Hb and Hct levels were comparable. The requirement of homologous blood transfusion in group I was significantly low (p<0.0001). Need for homologous transfusion was 0.72 per patient treated in the Group I. Conclusions: Acute normovolemic hemodilution is a simple, safe and effective modality to reduce perioperative transfusion of banked blood and should be considered in patients undergoing surgical procedures where major blood loss is expected.